213 A Novel, Cost-Effective and Convenient Model for Simulating Facial Wound Repair. (4th May 2021) - Rowe, A; Rapaport, B; Al-Najjar, Y; Chaudhry, B; Leow, J; Thomas, S
Abstract: Introduction: We describe the use of a novel synthetic simulation pad for learning complex facial wound management including local flaps. The simulation pad is a cost effective and convenient model of facial wounds. We have compared the use of animal tissue to the simulation pad in the context of a workshop for surgical trainees and collected feedback from delegates. Methods: Feedback was collected from 14 of 16 attending delegates. Results: It was clear from feedback that animal tissue is not an ideal model of facial wounds with 71% of delegates stating that they did not consider it to be high-fidelity. The synthetic pad was rated more favourably with 100% of delegates reporting that it was a valuable exercise and well designed for local flaps. Conclusions: It is imperative that training opportunities are high quality and useful to clinical practice. Techniques learnt in the context of a course or workshop are more valuable where targeted practice may occur following learning. The use of a synthetic pad is more amenable to continued practice where it may be taken home following a workshop. Feedback from this event suggests a well-designed synthetic pad is more useful than animal tissue in learning local flaps.